Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To find the equation of the line tangent to the graph of the function [tex]\( G(x) = 3e^{-5x} \)[/tex] at the point [tex]\( (0, 3) \)[/tex], we need to determine two key pieces of information: the slope of the tangent line at that point and the y-intercept of the tangent line.
### Step 1: Find the Slope of the Tangent Line
The slope of the tangent line at a point on a function's graph is given by the derivative of the function evaluated at that point. We first need to find the derivative of [tex]\( G(x) \)[/tex]:
[tex]\[ G(x) = 3e^{-5x} \][/tex]
Differentiate [tex]\( G(x) \)[/tex] with respect to [tex]\( x \)[/tex]:
[tex]\[ G'(x) = \frac{d}{dx}[3e^{-5x}] \][/tex]
Using the chain rule, we get:
[tex]\[ G'(x) = 3 \cdot \frac{d}{dx}[e^{-5x}] = 3 \cdot (-5e^{-5x}) = -15e^{-5x} \][/tex]
Next, we evaluate [tex]\( G'(x) \)[/tex] at [tex]\( x = 0 \)[/tex]:
[tex]\[ G'(0) = -15e^{-5(0)} = -15e^{0} = -15 \][/tex]
So, the slope of the tangent line at the point [tex]\( (0, 3) \)[/tex] is [tex]\(-15\)[/tex].
### Step 2: Find the Y-Intercept of the Tangent Line
The point-slope form of the equation of the tangent line is given by:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
where [tex]\( m \)[/tex] is the slope and [tex]\( (x_1, y_1) \)[/tex] is the given point on the curve.
Given:
- The slope [tex]\( m = -15 \)[/tex]
- The point [tex]\( (x_1, y_1) = (0, 3) \)[/tex]
Substitute these values into the point-slope form:
[tex]\[ y - 3 = -15(x - 0) \][/tex]
Simplify this equation to get the slope-intercept form:
[tex]\[ y - 3 = -15x \][/tex]
Add 3 to both sides to solve for [tex]\( y \)[/tex]:
[tex]\[ y = -15x + 3 \][/tex]
Thus, the equation of the line tangent to the graph of [tex]\( G(x) \)[/tex] at the point [tex]\( (0, 3) \)[/tex] is:
[tex]\[ y = -15x + 3 \][/tex]
### Step 1: Find the Slope of the Tangent Line
The slope of the tangent line at a point on a function's graph is given by the derivative of the function evaluated at that point. We first need to find the derivative of [tex]\( G(x) \)[/tex]:
[tex]\[ G(x) = 3e^{-5x} \][/tex]
Differentiate [tex]\( G(x) \)[/tex] with respect to [tex]\( x \)[/tex]:
[tex]\[ G'(x) = \frac{d}{dx}[3e^{-5x}] \][/tex]
Using the chain rule, we get:
[tex]\[ G'(x) = 3 \cdot \frac{d}{dx}[e^{-5x}] = 3 \cdot (-5e^{-5x}) = -15e^{-5x} \][/tex]
Next, we evaluate [tex]\( G'(x) \)[/tex] at [tex]\( x = 0 \)[/tex]:
[tex]\[ G'(0) = -15e^{-5(0)} = -15e^{0} = -15 \][/tex]
So, the slope of the tangent line at the point [tex]\( (0, 3) \)[/tex] is [tex]\(-15\)[/tex].
### Step 2: Find the Y-Intercept of the Tangent Line
The point-slope form of the equation of the tangent line is given by:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
where [tex]\( m \)[/tex] is the slope and [tex]\( (x_1, y_1) \)[/tex] is the given point on the curve.
Given:
- The slope [tex]\( m = -15 \)[/tex]
- The point [tex]\( (x_1, y_1) = (0, 3) \)[/tex]
Substitute these values into the point-slope form:
[tex]\[ y - 3 = -15(x - 0) \][/tex]
Simplify this equation to get the slope-intercept form:
[tex]\[ y - 3 = -15x \][/tex]
Add 3 to both sides to solve for [tex]\( y \)[/tex]:
[tex]\[ y = -15x + 3 \][/tex]
Thus, the equation of the line tangent to the graph of [tex]\( G(x) \)[/tex] at the point [tex]\( (0, 3) \)[/tex] is:
[tex]\[ y = -15x + 3 \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.